Economics of Fresh Water Prawn Farming in Southwest Region of Bangladesh - Yasmin, F; Hossain, M; Islam, MS; Rashid, MHA (Progressive Agriculture, 2013)
This study was designed to assess the profitability of freshwater prawn farming in gher systems in southwest Bangladesh. Four Upazilas namely: Bagerhat Sadar, Fakirhat, Mollahat and Chitalmari were purposely selected from Bagerhat district. Primary data were collected from randomly selected 100 gher owners. Results of the financial analyses indicate that investment in all the selected golda farming projects is profitable. On an average, total cost of FPF was Tk. 80,301.00 per hectare and average gross return per hectare per year stood at Tk. 216,400.00 and the gross margin per hectare per year was Tk. 205,278.00. The net return per hectare per year was Tk. 136,099.00. Although farmers in the study areas were facing different problems, it was concluded that the freshwater prawn farming is sustainable and it did not have any deleterious effect on environment. Finally, based on the findings of the study, some recommendations were made for the development of sound freshwater prawn farming in Bangladesh. DOI: http://dx.doi.org/10.3329/pa.v21i1-2.16779 Progress. Agric. 21(1 & 2): 223 - 231, 2010